Do Central Banks Respond Timely to Developments in the Global Economy? - Hilde C. Bjørnland; Leif Anders Thorsrud; Sepideh Khayati Zahiri (Norges Bank, 2016)
Our analysis suggests; they do not! To arrive at this conclusion we construct a real-time data set of interest rate projections from central banks in three small open economies; New Zealand, Norway, and Sweden, and analyze if revisions to these projections (i.e., forward guidance) can be predicted by timely information. Doing so, we find a systematic role for forward looking international indicators in predicting the revisions to the interest rate projections in all countries. In contrast, using similar indexes for the domestic economy yields largely insignificant results. Furthermore, we find that revisions to forward guidance matter. Using a VAR identified with external instruments based on forecast errors from the predictive regressions, we show that the responses to output, inflation, the exchange rate and asset returns resemble those one typically associates with a conventional monetary policy shock.
hdl:11250/2495709
Keywords: C11; C53; C55; E58; F17; 330; monetary policy; interest rate path; forecast revisions; global indicators